2023
DOI: 10.12965/jer.2244572.286
|View full text |Cite
|
Sign up to set email alerts
|

Gluteus medius muscle strengthening exercise effects on medial longitudinal arch height in individuals with flexible flatfoot: a randomized controlled trial

Abstract: This study aimed to compare the effects of 8 weeks of foot plus hip exercise to foot exercise alone on medial longitudinal arch (MLA) parameters; navicular drop (ND), arch height index (AHI), plantar pressure, static balance, and dynamic balance were measured at baseline, 4 weeks, and 8 weeks. A total of 52 healthy participants with bilateral flatfoot were randomly assigned into foot exercise (n= 26) and foot plus hip exercise (n= 26) group. At 4 weeks, the foot plus hip exercise group showed significantly les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…They reported that gluteus maximus strengthening exercises were important in recovering navicular drop and providing a typical gait pattern. Engkananuwat et al [ 32 ] evaluated the effects of performing gluteus medius strengthening exercises in addition to foot exercises in individuals with flexible pes planus. For 4 weeks, one group performed the short foot exercise and the other group performed a hip-strengthening exercise in addition to the foot exercise.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that gluteus maximus strengthening exercises were important in recovering navicular drop and providing a typical gait pattern. Engkananuwat et al [ 32 ] evaluated the effects of performing gluteus medius strengthening exercises in addition to foot exercises in individuals with flexible pes planus. For 4 weeks, one group performed the short foot exercise and the other group performed a hip-strengthening exercise in addition to the foot exercise.…”
Section: Discussionmentioning
confidence: 99%
“…125 A similar redistribution of plantar pressure was also found in previous studies after participants exercised tibialis posterior and intrinsic foot muscles. 27,126 The plantar pressure after wearing foot orthoses is commonly examined by in-shoe measuring system which differs from the current study. The results are therefore interpreted differently.…”
Section: Discussionmentioning
confidence: 99%